Doxycycline-containing glass ionomer cement for arresting residual caries: an in vitro study and a pilot trial - Aline Rogéria Freire de Castilho; Cristiane Duque; Paula Fernanda Kreling; Jesse Augusto Pereira; Andreia Bolzan de Paula; Mario Alexandre Coelho Sinhoreti; Regina Maria Puppin-Rontani (University of São Paulo, 2018)
Abstract In a previous study, we demonstrated that the incorporation of doxycycline hyclate (DOX) into resin-modified glass ionomer cement (RMGIC) inhibited important cariogenic microorganisms, without modifying its biological and mechanical characteristics. In this study, we keep focused on the effect of that experimental material as a potential therapy for arresting residual caries by analyzing other in vitro properties and conducting a pilot clinical trial assessing the in vivo effect of DOX-containing RMGIC on residual mutans streptococci after partial carious removal in primary molars. Specimens of the groups RMGIC (control); RMGIC + 1.5% DOX; RMGIC + 3% DOX; and RMGIC + 4.5% DOX were made to evaluate the effect of DOX incorporation on surface microhardness and fluoride release of RMGIC and against biofilm of Streptococcus mutans. Clinical intervention consisted of partial caries removal comparing RMGIC and RMGIC + 4.5% DOX as lining materials. After 3 months, clinical and microbiologic evaluations were performed. Data were submitted to ANOVA/Tukey or Wilcoxon/Mann-Whitney set as α=0.05. Fluoride release and surface microhardness was not influenced by the incorporation of DOX (p>0.05). There was a significant reduction of S. mutans biofilm over the material surface with the increase of DOX concentration. After clinical trial, the remaining dentin was hard and dry. Additionally, mutans streptococci were completely eliminated after 3 months of treatment with RMGIC + 4.5% DOX. The incorporation of DOX provided better antibiofilm effect, without jeopardizing fluoride release and surface microhardness of RMGIC. This combination also improved the in vivo shortterm microbiological effect of RMGIC after partial caries removal.